LIJEČENJE RUPTURE AHILOVE TETIVE MODIFIKOVANOM PERKUTANOM TEHNIKOM KOD SPORTISTA - Miroslav Kezunović; Žarko Dašić; Budimir Šegrt (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
With growing interest in sport activities of middle-age people in our population, we obtanied a high incidence of ruptures of Achilles tendon during last decade. It was usually preceded by its degenerative changes. Our aim was to examinate results of treatment of Achilles tendon rupture in group treated with our modified percutaneous technique with double crossed suture. We compared results with respondent delivered apply of nonsurgical method versus open surgical method. A total of our139 treated patients obtained injuries during their sport activities, vhether they were professionals or active or ex active, that are still in sport for recreation, or amateurs who are playing sports just for recreation. We also analised difference of the results of those three groups after the treatment and checked them statisticaly. Results had showed superirority of this percutaneous operative treatment because of its simple operative technique, posibility of doing it in local anesthesia, continous ultrasonographic following of rupture healing up of rupture and shorter taking of imobilisation, practicaly without hospitalization and with fewer complications.